Organization of Rental of Cars Abroad for Tourism - Xumoyunmirzo, Poziljanov (International Journal on Human-Computing Studies, 2023)
Car rental services ("Rent-a-car") is one of the most profitable activities related to the tourist business in the world. Their essence is that any citizen of a certain age can contact a car rental company and get a car with or without a driver for temporary use.